An empirical analysis of the determinants of bank's credit risk and evaluating the relationship between these determinants and the credit risk - Feng, Shu-Xin (2015)
The credit risk is one of the main risks for the banking industry. This kind of risk can be measured by banks’ non-performing loans in their balance sheets. This dissertation aims to explore the macroeconomic determinants and microeconomic determinants of banking credit risk for the European Union (EU) banking systems during the period of 2000 - 2015. Methodologically, this dissertation employs a statical panel data approach to examine the relationships between banking credit risk and its macroeconomic and microeconomic determinants. For the secondary data used in this empirical model, they were collected from Bankscope database, the World Bank database and International Financial Statistics (IFS) database. According to the empirical result, it can be concluded that banking credit risk can be significantly influenced by both macroeconomic factors and microeconomic factors. The macroeconomic factors include GDP growth rate, interest rate, exchange rate, inflation and unemployment rate. Thereinto, inflation and interest rate are significantly negatively related to banking credit risk, and unemployment rate are significantly positively related to credit risk. In terms of the bank-specific determinants, loan loss provision and solvency ratio have the significant positive relationship with credit risk, and they have significant negative relationships with credit risk. Finally, the findings of this dissertation indicate that the policy measures should be implemented to control the unemployment rate and inflation that in order to reducing public obligation, they are the fundamental of keeping economic and financial stability.